Invariant Approximation Results via Common Fixed Point Theorems for Generalized Weak Contraction Maps - Savita Rathee; Anil Kumar; Kenan Tas (Abstract and Applied Analysis)
A common fixed point theorem for generalized φ,ϕ,L f,g-weak contraction in a metric space is established. As an application, some common fixed point results in normed linear spaces are obtained. We also study some results on best approximation via common fixed point theorems. Our result improves some results from the existing literature. Some illustrative examples to highlight the realized improvements are also furnished.